Mycobacterium avium subspecies paratuberculosis is widely distributed in British soils and waters: implications for animal and human health. (6th May 2013) - Rhodes, Glenn; Henrys, Peter; Thomson, Bruce C.; Pickup, Roger W.
Summary In the first comprehensive geographical survey of distribution in Great Britain, Mycobacterium avium ssp. paratuberculosis (MAP) was detected in 115 of 1092 (10.5%) soil cores, in the range of 5 × 102 to 3 × 106 MAP cell equivalents (CE) g−1 wet weight soil with the majority of the positive PCR reactions (n = 75; 65%) occurring around the limit of detection (500–5000 CE g−1 wet weight soil). The distribution of MAP significantly increased from North to South and was significantly correlated with increasing cattle numbers over the same longitudinal axis. Similarly MAP occurrence significantly increased towards easterly latitudes although none of the parameters measured were associated. Comparisons of land use indicated that MAP was widely distributed in both farming and non‐farming areas. Soil core samples taken from the rivers Wyre and Douglas catchments (Lancashire, UK) and river Tywi (South Wales) were negative for MAP. However, river monitoring showed a consistent presence of MAPs throughout those catchments over a 6‐month period. We concluded that MAP is widely distributed within and outside the confines of the farming environment; its geographical distribution is wider than originally anticipated and; monitoring rivers describes the MAP status of catchment better than individual soil samples.